Are Competitors Forward Looking in Strategic Interactions? Evidence from the Field - Mario Lackner; Rudi Stracke; Uwe Sunde; Rudolf Winter-Ebmer (Institute for the Study of Labor (IZA), 2015)
This paper investigates empirically whether decision makers are forward looking in dynamic strategic interactions. In particular, we test whether decision makers in multi-stage tournaments take heterogeneity induced changes of continuation values and the ability of their immediate opponent into account when choosing effort. Using data from professional and semi-professional basketball tournaments, we find that effort is negatively affected by the ability of the current opponent, consistent with the theoretical prediction and previous evidence. More importantly, the results indicate that the expected relative strength in future interactions does affect behavior in earlier stages, which provides support for the 'standard' view that decision makers are forward looking in dynamic strategic interactions.
Keywords: D84; D90; M51; J33; 330; promotion tournament; multi-stage contest; elimination; heterogeneity; forward-looking behavior